2019
DOI: 10.1016/j.reth.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of sirolimus treatment for intractable lymphatic anomalies: A study protocol for an open-label, single-arm, multicenter, prospective study (SILA)

Abstract: IntroductionLymphatic anomalies (LAs) refer to a group of diseases involving systemic dysplasia of lymphatic vessels. These lesions are classified as cystic lymphatic malformation (macrocystic, microcystic or mixed), generalized lymphatic anomaly, and Gorham–Stout disease. LAs occur mainly in childhood, and present with various symptoms including chronic airway problems, recurrent infection, and organ disorders. Individuals with LAs often experience progressively worsening symptoms with a deteriorating quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 15 publications
1
24
0
2
Order By: Relevance
“…Before administering sirolimus, zoledronic acid, interferon, or propranolol were given, indicating that the current therapeutic protocols are not uniform (Table 2). In addition to cases listed in Table 1, Ricci et al [23] and Ozeki et al [24] reported eight cases treated with sirolimus but did not provide clinical histories of these cases. Six of the eight cases responded well to sirolimus.…”
Section: Discussionmentioning
confidence: 99%
“…Before administering sirolimus, zoledronic acid, interferon, or propranolol were given, indicating that the current therapeutic protocols are not uniform (Table 2). In addition to cases listed in Table 1, Ricci et al [23] and Ozeki et al [24] reported eight cases treated with sirolimus but did not provide clinical histories of these cases. Six of the eight cases responded well to sirolimus.…”
Section: Discussionmentioning
confidence: 99%
“…1) Localized macrocystic LMs are effectively treated with sclerotherapy with sclerosing agents (doxycycline, OK432, ethanol, bleomycin, sodium tetradecyl sulfate), those involving the skin and mucosa may be treated with PDL, and those that are complicated or extensive can be treated with sirolimus alone or in combination with sclerotherapy. 3,5,8,27,[55][56][57] AVMs are direct connections of arteries to veins that bypass the capillary bed. [2][3][4][5]7,8) AVMs of the skin are very rare, present as reddish-pink patches progressing to a deep red color with skin thickening, and can be diagnosed by arterial palpation.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…mTOR is an important kinase in the progression of the cell cycle. The net result is immune suppression by inhibition of lymphocytes and decreased lymphangiomatous invasion by inhibition of lymphangiogenic growth factors (33,34). The betablocking agent propranolol has also been reported as therapeutic option for Gorham-Stout disease, possibly through lowering of VEGF-A levels (35).…”
Section: Treatmentmentioning
confidence: 99%